ASSOCIATION BETWEEN ANATOMICAL RESOLUTION AND FUNCTIONAL OUTCOMES IN THE MIVI-TRUST STUDIES USING OCRIPLASMIN TO TREAT SYMPTOMATIC VITREOMACULAR ADHESION/VITREOMACULAR TRACTION, INCLUDING WHEN ASSOCIATED WITH MACULAR HOLE. Issue 6 (June 2015) - Gandorfer, Arnd; Benz, Matthew S.; Haller, Julia A.; Stalmans, Peter; Pakola, Stephen J.; Girach, Aniz; Kampik, Anselm; Toth, Cynthia A.; Jaffe, Glenn J.
Abstract : Purpose: To evaluate visual function in patients with symptomatic vitreomacular adhesion (VMA)/vitreomacular traction including when associated with macular hole after ocriplasmin treatment, and the association between resolution of the underlying condition and improvement in visual function. Methods: Six hundred and fifty-two patients from 2 Phase 3 trials received a single intravitreal injection of ocriplasmin 125 μ g (n = 464) or placebo (n = 188). Mean and categorical changes from baseline in best-corrected visual acuity and 25-item Visual Function Questionnaire scores were used to evaluate visual function. Subgroups with VMA resolution and full-thickness macular hole closure were compared. Results: Overall, 42% of patients who achieved VMA resolution at Day 28 had a ≥2-line improvement in best-corrected visual acuity at Month 6, and 20% had a ≥3-line improvement. Likewise, 69% of patients with nonsurgical full-thickness macular hole closure at Day 28 had a ≥2-line improvement at Month 6, and 48% had a ≥3-line best-corrected visual acuity improvement. Mean improvements in 25-item Visual Function Questionnaire scores were associated with achieving VMA resolution and nonsurgical full-thickness macular hole closure. Conclusion: In patients with symptomatic VMA/vitreomacular traction, VMA resolution and nonsurgical full-thickness macular hole closure were each associated with improvements in visual function. Resolving the underlying anatomical condition in symptomatic VMA/vitreomacular traction will increase the probability of achieving a clinically meaningful improvement in visual function. Abstract : In 2 Phase 3 clinical trials, successful achievement of vitreomacular adhesion resolution and nonsurgical closure of full-thickness macular hole after intravitreal ocriplasmin injection were associated with improvements in visual function and improved Visual Function Questionnaire–25 scores.